PERANCANGAN SISTEM FONDASI DALAM BANGUNAN GEDUNG BERTINGKAT PADA TANAH LUNAK - , MOHD. AMIR HAMZAH HARAHAP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pile foundation is the foundation that has the purpose to continue the load of storey buildings to bed rock underneath. The received load will be retained by bearing capacity and frictional resistance depending on the depth of pile and pile types. On soft soil, foundation pile is preferred because it does not influence the soil water level. Hotel Grand using existing pile foundations in the form of cylindrical pile with the cross-sectional diameter d = 0.45 m. Redesign is done by using square pile with the cross-section width b = 0.5. In this design, Pile are planting at a depth of 15 m (on the inside of the building) and 18.5 m (to the edge of the building). Soil on the construction site of Grand Central is soft soil such as sand soil interspersed with thin layers of clay and there is peat soil above it. Soil on this location is water saturated soil, so pile foundation is a method that should be use. Exsisting allowed bearing capacity is Qa = 87 tons for L = 15 m and Qa = 92 tons for L = 18.5 m, with allowed lateral resistance H = 40 kN. Allowed bearing capacity and lateral resistance for redesign results is qa = 130 tons and H = 70 kN for L = 15 m, and L = 18.5 m